2008
DOI: 10.14411/fp.2008.012
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection with two genotypes of Cryptosporidium in red squirrels (Sciurus vulgaris) in Italy

Abstract: Abstract.We investigated the genotypes of Cryptosporidium infecting red squirrels (Sciurus vulgaris L.) in two areas of the Western Alps in Italy. Examination of 141 faecal samples from 70 red squirrels revealed oocysts of Cryptosporidium in 17 animals (24.3%). Based on 18S rRNA gene sequencing, two genotypes of Cryptosporidium species were found: 15 squirrels were positive for the Cryptosporidium ferret genotype and 2 for the Cryptosporidium chipmunk genotype I. The occurrence and intensity of Cryptosporidium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 27 publications
(37 reference statements)
5
35
0
Order By: Relevance
“…In the present study, 26.3% of red squirrels and 25.0% of Siberian chipmunks harbored the genotype, a result similar to that observed (21.4%) in red squirrels (S. vulgaris) in Italy (26). The Cryptosporidium chipmunk genotype I, previously reported in red squirrels, eastern squirrels, eastern chipmunks, and deer mice in the United States and Italy (12,26), was not detected in this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, 26.3% of red squirrels and 25.0% of Siberian chipmunks harbored the genotype, a result similar to that observed (21.4%) in red squirrels (S. vulgaris) in Italy (26). The Cryptosporidium chipmunk genotype I, previously reported in red squirrels, eastern squirrels, eastern chipmunks, and deer mice in the United States and Italy (12,26), was not detected in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The Cryptosporidium ferret genotype has been found in ferrets and red squirrels (Sciurus vulgaris) (26,50). In the present study, 26.3% of red squirrels and 25.0% of Siberian chipmunks harbored the genotype, a result similar to that observed (21.4%) in red squirrels (S. vulgaris) in Italy (26).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the reduced subtype diversity of Cryptosporidium chipmunk genotype I in Sweden is not clear. Europe has no chipmunks or deer mice and only one native squirrel species, the red squirrel (Sciurus vulgaris), which has been identified as a host for Cryptosporidium chipmunk genotype I (21). This reduced host diversity might be partially responsible for the limited subtype diversity of the Cryptosporidium chipmunk genotype I in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Clarification of the taxonomy of Cryptosporidium species can be useful to identity new species that can infect humans, to assess the public health significance of infected animals, and to identify vertebrate sources of contamination for the environment. A wide variety of terrestrial and aquatic wildlife species had been reported to be infected with different species and genotypes of Cryptosporidium (2,5,6,8,11). However, little is known about the epidemiology and molecular characterization of this coccidium parasite in squirrel populations, which often thrive in close contact with urban and rural human populations and on agricultural lands.…”
mentioning
confidence: 99%
“…However, little is known about the epidemiology and molecular characterization of this coccidium parasite in squirrel populations, which often thrive in close contact with urban and rural human populations and on agricultural lands. Previous work has identified Cryptosporidium infections in a gray squirrel (13), fox squirrels (4), flying squirrels (4), a 13-lined ground squirrel (4), red squirrels (8), and California ground squirrels (1,3). Ground-dwelling squirrels of the genus Spermophilus are ubiquitous in many agricultural and food-producing systems and can reach high densities on watersheds in the western United States that are used for municipal surface water supplies.…”
mentioning
confidence: 99%